Quelques pistes de réflexion pour une approche pragmatiste de l’écologie industrielle : l’exemple de l’agglomération dunkerquoise - Christophe Beaurain; Delphine Varlet (Développement Durable et Territoires)
In integration of environmental requirements by firms, industrial ecology is generally presented as one of the most ambitious fields of reflection and action. The theoretical base of industrial ecology is established today solidly around an “ecocentric” position, based on the analogy between the natural systems and the socioeconomic systems. However the implementation of the industrial ecology remains difficult to establish and the examples of industrial symbiosis remain limited. In front of these difficulties, we sketch the foundations of a pragmatic reading of industrial ecology, support us for it on the experience of industrial ecology led within the urban area of Dunkirk.